Eph receptor B4 is a regulator of estrogen receptor alpha in breast cancer cells. (31st May 2013) - Schmitt, Fee; Nguyen, Phuong-Hien; Gupta, Nibedita; Mayer, Doris
Abstract: Background : Estrogen receptor alpha (ER-α) plays an important role in breast cancer initiation and progression and represents a major target in cancer therapy. The expression and activity of ER-α is regulated by multiple mechanisms at the transcriptional and post-translational level. Interaction of tyrosine kinase receptor-activated signaling pathways with ER-α function has been reported. We previously performed a kinome-wide small interfering RNA high-throughput screen to identify novel protein kinases involved in the regulation of ER-α transcriptional activity in human breast cancer cells. Our screening analysis identified the Eph receptor tyrosine kinases (Eph) as potential positive regulators of ER-α. Results : In this study, we demonstrate Eph receptor B4 (EphB4), a member of Eph kinase family, a positive regulator of ER-α in human breast cancer cell lines (MCF-7, T-47D and BT-474). Down-regulation of EphB4 by RNA interference technology impairs estrogen-dependent ER-α transcriptional activity in breast cancer cells. Decreased activity of ER-α after EphB4 knockdown is the consequence of diminished ER-α messenger RNA and protein expression. Furthermore, phosphorylation of Akt, a downstream mediator of EphB4, is reduced following EphB4 silencing. Conclusions : Our data suggests EphB4 as an upstream regulator of ER-α in human breast cancer cells by modulating ER-α transcription. The results also suggest Akt as a relevant downstream signaling molecule in this novel EphB4-ER-α pathway.